Peran Guru dalam Memfasilitasi Proses Belajar dan Perkembangan Peserta Didik di MI Nurul Islam Sukosari Lumajang - Mutmainah, Siti (Ibtida'iy : Jurnal Prodi PGMI, 2025)
Teachers have a strategic role in facilitating the learning process and supporting the development of students holistically, both in terms of academics and character. This study aims to analyze the role of teachers in facilitating learning and student development at MI Nurul Islam Sukosari, Lumajang. This research uses descriptive qualitative method with data collection techniques in the form of interviews, observations, and documentation. The results showed that the teacher acts as a facilitator, motivator, and guide. As facilitators, teachers provide innovative learning media and methods to increase student engagement. As a motivator, teachers provide emotional encouragement and appreciation to build students' confidence. As mentors, teachers help students overcome learning difficulties and personal problems. However, teachers face challenges such as limited time, facilities and variations in students' abilities. This study concludes that an optimal teacher role can create a conducive learning environment and support the overall development of learners.